Numerical Simulation on the Local Scour Processing and Influencing Factors of Submarine Pipeline - Ke Hu; Xinglan Bai; Murilo A. Vaz (Journal of Marine Science and Engineering, 2023)
To investigate the different influencing characteristics of local scour around submarine pipelines, hydrodynamic and sediment transport two-dimensional models based on Flow-3D are used to numerically simulate the local scour around the pipeline under steady currents. An RNG k-ε turbulence model is applied to simulate the turbulent flow field around the pipeline. The instantaneous shear stress of the bed surface is taken as the starting and transporting conditions of the sediment. The simulation results of the equilibrium scour depth and terrain around the pipeline are verified with the previous experimental results, which perform with good agreement. Then, the numerical simulation method is applied to investigate the local scour process around the pipeline. The results show that shear stress is the main driving force of scour around a pipeline. The velocity, sediment grain size, pipeline diameter, and the initial gap between the pipeline and the seabed, significantly affects submarine pipeline equilibrium scour depth and terrain in varying degrees.